Developing Speaking Material Using Islamic contents in MA Salafiyah Kajen - Nikmah, Alfu (Journal of English Teaching and Learning Issues, 2018)
This article tries to describe about the developing Islamic content textbook for speaking English. The method used in this article are developmental research and design instructional model for the design. The article is not to generate a theory or verify one. It attempts to develop English learning material for speaking skill using textbook containing Islamic contents at first semester of tenth grade senior high school. Some steps passed in developing the English vocabulary material; need analysis, design, development, expert validation, try out, revision, and final product. It could be as a proof that this material could be applied to the tenth grade students. And the result shows that Islamic content textbook for English speaking material could be applied to the tenth grade students in Madrasah Aliyah Salafiyah Kajen, Pati Central Java Indonesia.